Cocktail of Astragalus Membranaceus and Radix Trichosanthis Suppresses Melanoma Tumor Growth and Cell Migration Through Regulation of Akt-Related Signaling Pathway - Zhang, Qiuyan; Gao, Lei; Huang, Songli; Liang, Yuxi; Hu, Jingyan; Zhang, Yuan; Wei, Shengli; Hu, Xiuhua (Frontiers in Pharmacology, 2022)
Background: Malignant Melanoma has high morbidity and mortality, and limited treatment options. Now traditional Chinese medicine has been widely and effectively used in the clinical therapy of cancer, and the theory of compatibility is one core content of Chinese medical theory. Astragalus Membranaceus and Radix Trichosanthis are clinically effective for the treatment of various cancers. Methods: We verified the effects of AMD, RTD and their compatibility on melanoma model in vitro and vivo and the mechanism of its effect on Akt related signaling pathway by Network pharmacology, MTT, Flow Cytometry, LDH, SOD and MDA Assay and Western Blot. Results: The network pharmacology analysis indicated that PI3K-Akt pathway plays a crucial role in the treatment of malignant melanoma with these two herbs. In addition, AMD, RTD and their “cocktail” could inhibit the proliferation of A375 cells by reducing the survival rate with concentration dependent and regulating the cell cycle, and the compatibility of two herbs also could inhibit melanoma growth. They could respectively induce apoptosis and inhibit migration by affecting the expression of Bcl-2, Bax, p53 and snail, E-cadherin, N-cadherin. Furthermore, LDH activity was decreased, while SOD increased, MDA reduced. The factors of Akt related signaling pathway, Akt and p-Akt, were decreased. Conclusion: This study showed that AMD, RTD and their “cocktail” could regulate cell proliferation, apoptosis and metastasis in A375 cells through suppression of Akt related signaling pathway, and the compatibility group had detoxication and synergism effects. The best compatibility of the two herbs also can inhibit tumor growth and metastasis in vivo.